ANALISIS TINGKAT DEPRESI PADA SISWI SMK MUHAMMADIYAH KABUPATEN WONOGIRI - Susana Nurtanti (Akademi Keperawatan Giri Satria Husada Wonogiri, 2021)
Background: The problems of depression have become health challenges in almost all over the world, including in Indonesia. Objective: The purpose of this study was to determine the prevalence level of depression in adolescent at SMK Muhammadiyah Baturetno, Wonogiri Regency, Indonesia. Method: The design of this study was a descriptive quantitative study with a cross-sectional approach. The instrument in this study used a questionnaire about DASS42. Results: Most of the respondents of the study the prevalence of depression was 35 (12.1%), anxiety was 115 (39.8%) and stress was 139 (48.1%). Conclusion: From the results of the study, the prevalence of depression was 35 (12.1%), anxiety was 115 (39.8%) and stress was 139 (48.1%). Latar belakang: Permasalahan depresi menjadi tantangan kesehatan hampir di seluruh dunia, termasuk di Indonesia. Tujuan: Tujuan penelitian ini adalah untuk mengetahui tingkat prevalensi depresi pada remaja siswi di SMK Muhammadiyah Baturetno Kabupaten Wonogiri Indonesia. Metode: Desain penelitian ini adalah penelitian kuantitatif deskriptif dengan pendekatan cross-sectional. Instrumen dalam penelitian ini menggunakan kuesioner tentang DASS42. Hasil: Secara umum maka maka prevalensi depresi sejumlah 35 (12,1%), ansietas sejumlah 115 (39,8%) dan stress sejumlah 139 (48,1%). Kesimpulan: Dari hasil penelitian prevalensi depresi sejumlah 35 (12,1%), ansietas sejumlah 115 (39,8%) dan stres sejumlah 139 (48,1%).